2017
DOI: 10.1021/acs.jpcc.7b04886
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Moment Controlling Desorption Temperature in Hydrogen Storage: A Case of Zirconium-Doped Graphene as a High Capacity Hydrogen Storage Medium

Abstract: For the first time, we predict through density functional theory that a single Zr atom attached on graphene surface can adsorb maximum of 9 H2 molecules with average binding energy of 0.34 eV and average desorption temperature of 433 K leading to a wt % of 11, higher than the DoE’s requirement of 6.5 wt %.The dependency of desorption temperature (T D ) of H2 molecule with the magnetic moment (μ) of the system was exclusively studied by formulating the empirical relation T D = T 0 + aμ b (with T 0 = 399 K,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 69 publications
(36 citation statements)
references
References 43 publications
(73 reference statements)
2
34
0
Order By: Relevance
“…According to Wang et al, Li-decorated porous graphene can reach a H 2 storage capacity of 10.89 wt % at T = 300 K with no external pressure. 32 wt % for zirconium-doped graphene, 1 which is much higher than the DOE target. Ao et al 33 35 Despite the high gravimetric densities reported earlier in the literature related to the positive effect of Nb in functionalizing different structures for hydrogen storage, the H 2 storage capacity on bar niobium (Nb) and niobium-functionalized graphene (GR@Nb) has not been addressed.…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations
“…According to Wang et al, Li-decorated porous graphene can reach a H 2 storage capacity of 10.89 wt % at T = 300 K with no external pressure. 32 wt % for zirconium-doped graphene, 1 which is much higher than the DOE target. Ao et al 33 35 Despite the high gravimetric densities reported earlier in the literature related to the positive effect of Nb in functionalizing different structures for hydrogen storage, the H 2 storage capacity on bar niobium (Nb) and niobium-functionalized graphene (GR@Nb) has not been addressed.…”
Section: Introductionmentioning
confidence: 94%
“…Liquid-state and high-pressure tanks are problematic due to the cost of liquefaction, excessive loss of hydrogen, risk of explosion at high pressure, and the great weight of high-pressure containers. Solid-state storage of hydrogen is the most promising method . In this view, the U.S. Department of Energy (DOE) has established the criteria for a sorbent to be considered for mobile application.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared with the hydrogen storage technologies of high pressure tank and liquid state storage, which are limited by the large size and weight of the tank and the high cost for liquefaction, the solid state storage has become a popular technology which can storage hydrogen by providing storage mediums and release it without changing the structure of mediums. A large amount of work has proved that carbon nanostructures (including carbon fullerenes, carbon nanotubes and graphyne), which decorated by the alkali metal atoms, [30][31][32][33][34] alkaline-earth metal atoms [35][36][37][38] and transition-metal atoms, [39][40][41][42][43][44] can be the promising hydrogen storage mediums. Similarly, boron nanostructures decorated by the metal atoms can also be applied in hydrogen storage.…”
Section: Introductionmentioning
confidence: 99%